Collection, Storage and Retrieval of Geological Held Data in Precambrien and Paleozoic Rocks of Southern New Brunswick - Ruitenberg, A.; Chandra, J.; Secord, D. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary Large amounts of geologic field data have been produced as a result of recent geologic investigations by the New Brunswick Department of Natural Resources, financed by the Federal Department of Regional Economic Expansion. This necessitated designing a standardized system for the collection, storage and retrieval of geologic field data, which is briefly described in this report.